Diversity in Social Communication and Support: Implications for Loneliness Among LGB Adults. (21st July 2022) - Peterson, Natasha; Lee, Jeongeun; Svec, Joseph; Russell, Daniel
Abstract: Background and Objectives: Current research indicates that structural and functional social network attributes influence older adults' well-being. However, these linkages may vary by sexual orientation. This study examines how social communication diversity and support diversity are related to loneliness and differ between lesbian, gay, and bisexual (LGB) and heterosexual adults. Research Design and Methods: Using data from the American Association of Retired Persons Foundation's Loneliness and Social Connection Survey of adults 45+ ( N = 3, 009), including 10% who identified as LGB, we derive entropy scores, which capture the extent to which network size and quality of relationships are evenly distributed. A series of linear regressions were conducted to examine sexual orientation, social network indicators, and their interactions in predicting loneliness. Results: We found a positive association between social communication diversity and loneliness. This finding was qualified by the interaction with sexual orientation. In addition, we found a negative association between support diversity and loneliness, an effect that was stronger for LGB participants than for heterosexual participants. The effect of support diversity on loneliness was much stronger for LGB adults than heterosexual adults. Discussion and Implications: While LGB adults tend to score higher on the loneliness scale overall, the findings suggest that communication and support diversity have uniquely different patterns of associations for sexual minority groups. This study highlights the importance of considering multiple dimensions of social networks and has implications for addressing loneliness for heterosexual and LGB adults.